Polarimetric Properties of Event Horizon Telescope Targets from ALMA - Goddi Ciriaco; Martí-Vidal Iván; Messias Hugo; Bower Geoffrey C.; Broderick Avery E.; Dexter Jason; Marrone Daniel P.; Moscibrodzka Monika; Nagai Hiroshi; Algaba Juan Carlos; Asada Keiichi; Crew Geoffrey B.; et al. (IOP PUBLISHING LTD, 2022)
We present the results from a full polarization study carried out with the Atacama Large Millimeter/submillimeter Array (ALMA) during the first Very Long Baseline Interferometry (VLBI) campaign, which was conducted in 2017 April in the λ3 mm and λ1.3 mm bands, in concert with the Global mm-VLBI Array (GMVA) and the Event Horizon Telescope (EHT), respectively. We determine the polarization and Faraday properties of all VLBI targets, including Sgr A*, M87, and a dozen radio-loud active galactic nuclei (AGNs), in the two bands at several epochs in a time window of 10 days. We detect high linear polarization fractions (2%-15%) and large rotation measures (RM > 103.3-105.5 rad m-2), confirming the trends of previous AGN studies at millimeter wavelengths. We find that blazars are more strongly polarized than other AGNs in the sample, while exhibiting (on average) order-of-magnitude lower RM values, consistent with the AGN viewing angle unification scheme. For Sgr A* we report a mean RM of (-4.2 0.3) x 105 rad m-2 at 1.3 mm, consistent with measurements over the past decade and, for the first time, an RM of (-2.1 0.1) x 105 rad m-2 at 3 mm, suggesting that about half of the Faraday rotation at 1.3 mm may occur between the 3 mm photosphere and the 1.3 mm source. We also report the first unambiguous measurement of RM toward the M87 nucleus at millimeter wavelengths, which undergoes significant changes in magnitude and sign reversals on a one year timescale, spanning the range from -1.2 to 0.3 x 105 rad m-2 at 3 mm and -4.1 to 1.5 x 105 rad m-2 at 1.3 mm. Given this time variability, we argue that, unlike the case of Sgr A*, the RM in M87 does not provide an accurate estimate of the mass accretion rate onto the black hole. We put forward a two-component model, comprised of a variable compact region and a static extended region, that can simultaneously explain the polarimetric properties observed by both the EHT (on horizon scales) and ALMA (which observes the combined emission from both components). These measurements provide critical constraints for the calibration, analysis, and interpretation of simultaneously obtained VLBI data with the EHT and GMVA.